2003
DOI: 10.3168/jds.s0022-0302(03)73993-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Levels of Gum Arabic, Low Methylated Pectin and Xylan on In Vitro Digestibility of β-Lactoglobulin

Abstract: Plant hydrocolloids used in the food industry to improve texture and stability of food, such as dairy products, can reduce protein digestibility and, consequently, modify the bioavailability of amino acids. We studied the in vitro hydrolysis at 37 degrees C of beta-lactoglobulin (beta-lg) in mixed dispersions containing either gum arabic or low-methylated pectin or xylan at levels of 0, 1, 10, 20, 30, and 50% weight. Proteolysis used either pepsin alone by progressive reduction of pH during proteolysis or peps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
5
17
2
Order By: Relevance
“…The absence of a difference in N release from protein without polysaccharides through the two dialysis bags was also obtained with b-lactoglobulin, a globulin protein of whey milk (Mou ecoucou et al, 2003), suggesting that proteins were mainly hydrolyzed in to low MW peptides (<1000 Da) so increasing the porosity of the membrane did not greatly change the results. Conversely, the electrophoresis patterns of PPI without polysaccharide showed slight difference between the retentates from the two dialysis bags.…”
Section: Discussionmentioning
confidence: 70%
“…The absence of a difference in N release from protein without polysaccharides through the two dialysis bags was also obtained with b-lactoglobulin, a globulin protein of whey milk (Mou ecoucou et al, 2003), suggesting that proteins were mainly hydrolyzed in to low MW peptides (<1000 Da) so increasing the porosity of the membrane did not greatly change the results. Conversely, the electrophoresis patterns of PPI without polysaccharide showed slight difference between the retentates from the two dialysis bags.…”
Section: Discussionmentioning
confidence: 70%
“…The nature of the polysaccharides plays a major role in the interaction between protein and polysaccharides. In this way, Mouecoucou et al, 2003 and2004, have shown that xylan, arabic gum and pectin prevented hydrolysis of β-lactoglobulin or peanut protein isolate, differently according to their nature.…”
Section: Discussionmentioning
confidence: 93%
“…Of the 2 well‐known proteolytic enzymes, trypsin and chymotrypsin, trypsin specifically cleaves peptide bonds after the N‐terminal of lysine and/or arginine residues, while chymotrypsin specifically cleaves peptide bonds after tyrosine, tryptophan, phenylalanine, leucine, and/or methionine residues (Margoliash and Smith 1962; Mouécoucou and others 2003). The enzyme of B. subtilis DB was found to potentially cleave peptide bonds after the N‐terminal of leucine, glutamine, lysine, threonine, and phenylalanine.…”
Section: Resultsmentioning
confidence: 99%